Discovery of 3-phenyl-1, 2, 4-oxadiazole derivatives as a new class of SARS-CoV-2 main protease inhibitors. (15th April 2023) - Guo, Nihong; Huang, Chong; Qiao, Jingxin; Li, Yueyue; Wang, Yifei; Xia, Anjie; Zhang, Guo; Fang, Zhen; You, Jing; Li, Linli
Graphical abstract: Abstract: The ongoing COVID-19 pandemic has led to massive infections and deaths and caused tremendous grief among the people. Although vaccines have played an important role in fighting COVID-19, the situation that the protective effect of current vaccines significantly decreases against mutated strains reminds us of the pressing need for developing effective antiviral therapeutics. The main protease (M pro ) is a key enzyme for SARS-CoV-2 viral replication and transcription and an attractive target for drug development. In this research, we report a new series of M pro inhibitors containing 3-phenyl-1, 2, 4-oxadiazole. Structure-activity relationship (SAR) studies led to the discovery of the most active compound, 16d, which showed an IC50 value of 5.27 ± 0.26 μM. Collectively, we obtained a new small molecular inhibitor targeting SARS-CoV-2 M pro, which contains a new scaffold. This compound could be taken as a lead compound for subsequent drug discovery against SARS-CoV-2.